SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS BASED ON BLENDED LEARNING FOR IMPROVING CRITICAL THINKING ABILITY OF STUDENTS - Safira, Ifa; Syam, Husain; Ahmad, Muhammad Arifin (Universitas Muhammadiyah Semarang, 2021)
This study aims to develop STEM (learning model Science, Technology, Engineering and Mathematics Based Blended Learning a practical). The problem posed is to produce a practical STEMBL model in terms of the implementation of learning, learning activities, lecturer responses and student responses. The STEMBL model was developed by adapting the Plomp development flow, namely (1) initial investigation; (2) design; (3) realization/construction; (4) tests, evaluations, and revisions and (5) implementation. The model components developed refer to Arend and the model criteria refer to Nieveen. The subjects of this study were PGSD students at the University of Bosowa. The practicality of the model data was obtained through the instrument implementation of the model, the implementation of learning, as well as learning activities offline and online. The results of this study indicate that the STEMBL model is declared practical based on the observations of the observer on the implementation of the model, learning management and student learning activities based on the results of the practitioner's assessment of the learning model. Based on the findings, it can be concluded that the STEMBL model is practical in improving students' critical thinking skills.Keywords: STEM, blended learning, critical thinking skills